How Children and Adolescents Perceive Their Coping With Home Learning in Times of COVID-19: A Mixed Method Approach - Simm, Inga; Winklhofer, Ursula; Naab, Thorsten; Langmeyer, Alexandra N.; Linberg, Anja (Frontiers in Psychology, 2021)
With the COVID-19 pandemic, children and adolescents were confronted with a completely new learning situation. Instead of learning in class, they had to cope with home learning to achieve aca-demically. This mixed-method study examines how children and adolescents in Germany perceive their coping success with home learning in times of the COVID-19 pandemic and how personal, school, family and peer context factors influence this self-perceived coping success. Quantitative data from an online survey of n= 141 children (mage = 10,8y) and n= 266 adolescents (mage = 15,2y) (study 1) was used to analyse this questions with multiple regression analysis. With the qualitative data from 10 interviews with parents and their children (study 2) we examined the process how school, family and peer group interact with students way of coping with home learning. Quantitative data shows that most children and adolescents perceived their coping with home learning as successful and that personal factors like cognitive and motivational-affective factors are still relevant for students learning at home. Qualitative data shows that students apply individual ways of coping with home learning, where family and peers have a vital role, especially when the contact with teachers is limited. Quantiative data confirms the importance of family context for students self-perceived coping success.